Policy versus Reality: Challenges of Implementing ICT in Higher Education in Nepal (Pragyaratna प्रज्ञारत्न, 2024)
This paper discusses the challenges of implementing information and communication technology (ICT) in higher education, comparing policy with reality in Nepal. Education is a socially oriented activity traditionally associated with strong teachers and personal contact with learners. ICT has become an integral part of today’s teaching and learning process. The efficient utilization of ICT can enhance student motivation, enhance class dynamics, and boost teacher enthusiasm as they acquire new skills and techniques. ICT in education significantly enhance teaching, learning, and research, preparing future generations for future careers and lives. However, the policy and reality of ICT use in higher education are increasingly crucial in the 1st century for enhancing teaching and learning by incorporating digital environment. This paper, based on reviews of secondary data from government and UGC sources, reveals disparities in the practical implementation of these policies. The findings revealed that the government of Nepal has implemented various ICT policies since the 1990s, including the ICT in education Master Plan, Higher Education Policy, Digital Nepal Framework, and NEHEP. All these policies initiatives aim to improve educational quality by integrating ICT into teaching, learning and administrative processes. Despite the implementation of comprehensive policies, significant challenges persist, including inadequate funding, inadequate infrastructure, and a lack of teacher training. This paper concludes that there is a need for a coordinated strategy, continuous investment, and robust monitoring to maximize the potential of ICT in higher education in Nepal.